PELAKSANAAN PEMBINAAN WARGA BINAAN MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Hutagalung, Nandito (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTThe Penitentiary is a place for guidance to the assisted residents. This is contained in Article 1 paragraph (3) of Law Number 12 the Year 1995, namely "Penitentiary, hereinafter referred to as LAPAS, is a place to carry out fostering of Assisted Citizens and Correctional Students".This coaching activity is solely to improve the quality of devotion to God Almighty, intellectual, attitudes and behavior, professional, physical, and spiritual health, carried out in an integrated manner between the coach, the fostered, and the community so that the Assisted Citizens realize their mistakes.The writing method is the procedure for how a study will be carried out. Based on what the author presents, the writer uses the Normative research method.Forms of coaching work skills, from the results of the research that the author got, there are various kinds of skills provided by the coach to the assisted residents.It is hoped that the correctional institutions can give attention to the assisted residents by conducting regular socialization about the law and the rights of the inmates at least once a month so that the inmates can understand the law. Keywords: Assisted Residents, Penitentiary